The Prognostic Effect of Clinical and Laboratory Findings on in-hospital Mortality in Patients with Confirmed COVID-19 Disease - Jangjou, Ali; Mousavi-Roknabadi, Razieh S.; Faramarzi, Hossein; Neydani, Alireza; Hosseini-Marvast, Seyed Rouhollah; Moqadas, Mostafa (Current Respiratory Medicine Reviews, 2022)
Background: COVID-19 is known as a global health issue, which can cause high morbidity and mortality in patients. It is necessary to identify biomarkers, clinical and laboratory findings and effects on patients' mortality. Objective: This study aimed to evaluate the prognostic effect of clinical and laboratory findings on in-hospital mortality in patients with confirmed COVID-19. Methods: This retrospective cross-sectional study (February-August 2020) was conducted on adult patients with COVID-19 who were hospitalized in one of the main reference hospitals affiliated with Shiraz University of Medical Sciences, southern Iran. Patients with uncompleted or missed medical files were excluded from the study. Clinical and laboratory findings were extracted from the patients' medical files and then analyzed. The patients were categorized and later compared as survivor and nonsurvivors groups. Results: 345 patients were enrolled and 205 (59.4%) were male. The mean±SD of age was 53.67±16.97 years, and 32 (9.3%) out of the total did not survive. Hypertension (28.4%) and diabetes (25.5%) were the most prevalent comorbidities. All clinical symptoms were similar in both groups, except fever, which was observed significantly more in nonsurvivors (P=0.027). The duration of hospitalization was 9.20±5.62 (range; 2-42) days, which was higher in nonsurvivors (P<0.001). The results of Multivariate Logistic Regression Model showed that CRP (OR=1.032, P=0.01) and INR (OR=48.88, P=0.049) were the predictor factors for in-hospital mortality in hospitalized patients with confirmed COVID-19. Conclusion: The current study showed that in-hospital mortality was 9.3%. It was found that CRP and INR were the predictor factors for in-hospital mortality in hospitalized patients with confirmed COVID-19.
Keywords: COVID-19